2022
DOI: 10.1055/s-0042-1749635
|View full text |Cite
|
Sign up to set email alerts
|

Mother to Newborn Transmission of SARS-CoV-2 Infection: Evolution of Evidence in 1.5 Years of COVID-19 Pandemic

Abstract: Coronavirus disease 2019 (COVID-19) pandemic caused significant mortality and morbidity in people of all age groups worldwide. Given the uncertainty regarding the mode of transmission and potential effects of COVID-19 on pregnant mothers and their newborns, guidelines for taking care of maternal–newborn dyads have evolved tremendously since the pandemic began. There has been an enormous influx of published materials regarding the outcomes of mothers and newborns. Still, multiple knowledge gaps regarding compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 134 publications
0
5
0
Order By: Relevance
“…Placental inflammation on available pathology in our cohort as well as in other placental pathological studies in the setting of SARS-CoV-2 infection suggests a potential mechanism for hypoxic-ischemic and/or perinatal infarct pattern of injury that was observed. 6,14 In one case, there was evidence of in utero white matter injury which could also reflect early placental dysfunction. A recent manuscript reported that the placentas of two infants with neurologic findings born to mothers positive for SARS-CoV-2 were positive for SARS-CoV-2 proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Placental inflammation on available pathology in our cohort as well as in other placental pathological studies in the setting of SARS-CoV-2 infection suggests a potential mechanism for hypoxic-ischemic and/or perinatal infarct pattern of injury that was observed. 6,14 In one case, there was evidence of in utero white matter injury which could also reflect early placental dysfunction. A recent manuscript reported that the placentas of two infants with neurologic findings born to mothers positive for SARS-CoV-2 were positive for SARS-CoV-2 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Vertical transmission of COVID has been shown to be rare. 6 A systemic inflammatory response, such as FIRS or MIS-N, is emerging as a potential source of neonatal morbidity and mortality in babies born to mothers with a history of COVID infection during pregnancy. 1 FIRS involves activation of the fetal immune response and the proposed mechanism of MIS-N is inflammation secondary to transplacental antibodies or cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data are still insufficient regarding whether women with COVID-19 can transmit the virus to their newborns during labor and breastfeeding [ 6 ]. Thus, the guidelines for taking care of mother–newborn dyads have changed significantly during the pandemic [ 7 ]. The concern of possible transmission of the virus from an infected mother to her infant led to the disruption of some practices recognized as crucial for maternal bonding and breastfeeding initiation, such as skin-to-skin contact and rooming-in [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Horizontal transmission of COVID-19 to a newborn can occur with the possibility of occurrence during perinatal exposure, from infected family members or hospital staff while still admitted, breastmilk and breastfeeding should be strongly encouraged for the newborns as the chances of passing SARS-CoV-2 infection from mother to newborn causing serious illness are extremely low, vaccinations of women who are pregnant, planning to become pregnant, or were recently pregnant is safe and protect mothers from serious consequences of COVID-19; and adequate (two doses) COVID-19 vaccination in mother especially during the late second trimester and third trimester provides passive protective antibodies to newborns and reduce the overall severity of COVID-19 infection in newborns. 5,[9][10][11][12] Some questions are yet to be adequately answered such as the outcomes of newborns and infants exposed to COVID-19 beyond the rst few months of life, the impact of COVID-19 on the post-discharge home care practices and challenges and the effect of COVID-19 on post-discharge healthcare utilizations visits and outcomes. These questions although are currently limited to the context of the current COVID-19 pandemic, they are extremely important to be looked upon and hopefully would be helpful in case of similar future outbreaks.…”
mentioning
confidence: 99%